2020
DOI: 10.1021/acsomega.0c00966
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Supercapacitors Prepared Using the Peanut-Shell-Based Carbon

Abstract: In this work, we report the fabrication and performance of supercapacitors made from carbonized peanut shells, which are renewable materials with a huge annual yield and are usually discarded directly by people. With proper treatment, peanut shells could be used for many applications. Herein, we demonstrate that the peanut shells treated with carbonization and activation processes not only possess an extremely high surface area but also provide a hierarchical structure for energy storage. The performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…This phenomenon is maybe connected with the relatively lower ionic mobility of EMIMBF 4 and LiPF 6 electrolytes, which have a higher viscosity. Besides, it can be easily found that the Nyquist plots of all supercapacitors are almost vertical lines at the low frequency region, manifesting that the supercapacitors possess a good ion diffusion/migration behavior and typical double-layer charge storage characteristic …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This phenomenon is maybe connected with the relatively lower ionic mobility of EMIMBF 4 and LiPF 6 electrolytes, which have a higher viscosity. Besides, it can be easily found that the Nyquist plots of all supercapacitors are almost vertical lines at the low frequency region, manifesting that the supercapacitors possess a good ion diffusion/migration behavior and typical double-layer charge storage characteristic …”
Section: Resultsmentioning
confidence: 95%
“…Besides, it can be easily found that the Nyquist plots of all supercapacitors are almost vertical lines at the low frequency region, manifesting that the supercapacitors possess a good ion diffusion/migration behavior and typical double-layer charge storage characteristic. 50 Figure 7b shows the capacitance−frequency plots in different electrolytes of the AHPCS supercapacitors, which appear as a series combination of capacitance and resistance in the EIS measure. The specific capacitance values are figured by eq 5: 49 C fZ m…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results demonstrate the great potential for using this very abundant negative-value shall waste of various types of nuts for the supercapacitor technology. [101][102][103]…”
Section: Production Of Graphene Oxide and Reduced Graphene Oxide From...mentioning
confidence: 99%
“…There have been some recent studies about the application of carbon derived from peanut shells in the energy storage system [20][21][22]. Jia et al [23] firstly reported their work about a hybrid sodium ion capacitor (NIC) being derived from peanut shells.…”
Section: Introductionmentioning
confidence: 99%